Weed Diversity in Sweet Corn (Zea mays Saccharata) Area with Different Observation Time in Tobelo Tengah District, North Halmahera - Kastanja, Ariance Yeane; Patty, Zeth (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
The research that has been carried out in Tobelo Tengah District aims to determine the types of weeds and their dominance. Weed identification was carried out using the quadratic method using rectangular plots. The results showed that the weeds found were almost uniform in each observation plot between different ages of observation at the observation site, while the weed families found were almost consistent in both locations namely Capparidiceae, Cyperaceae, Poaceae and Portulacaceae